2020
DOI: 10.1002/ehf2.12708
|View full text |Cite
|
Sign up to set email alerts
|

The novel urinary proteomic classifier HF1 has similar diagnostic and prognostic utility to BNP in heart failure

Abstract: Aims Measurement of B-type natriuretic peptide (BNP) or N-terminal pro-BNP is recommended as part of the diagnostic workup of patients with suspected heart failure (HF). We evaluated the diagnostic and prognostic utility of the novel urinary proteomic classifier HF1, compared with BNP, in HF. HF1 consists of 85 unique urinary peptide fragments thought, mainly, to reflect collagen turnover. Methods and results We performed urinary proteome analysis using capillary electrophoresis coupled with mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Previous studies indicated an association of biomarkers reflecting collagen turnover with heart failure 1,2 . However, their value in predicting unfavorable outcomes is unknown.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated an association of biomarkers reflecting collagen turnover with heart failure 1,2 . However, their value in predicting unfavorable outcomes is unknown.…”
Section: Figurementioning
confidence: 99%
“…The Ethics Committee of the University of Aachen approved the secondary use of anonymized data and the biomarker measurements (number EK163/19). Tianlin He 1,2 Jesus D. Melgarejo 3 Andrew L. Clark 4 Yu-Ling Yu 3 Lutgarde Thijs 3 Javier Díez 5,6,7 Begoña López 5,6,7 Arantxa González 5,6,7 John G. Cleland 8 Joost P. Schanstra 9,10 Antonia Vlahou 11 Agnieszka Latosinska 1 Harald Mischak 1,12 Jan A. Staessen 3,13 Zhen-Yu Zhang 3…”
Section: A C K N O W L E D G M E N Tmentioning
confidence: 99%
“…For each peptide, fold change in disease vs. controls was calculated. Similarly, the fold change was also assessed for HF, investigating 773 datasets from HF patients compared to 773 controls [15]. To define the changes observed in AKI, data from 94 patients with AKI (KDIGO grade 2 and 3) were compared to controls (KDIGO grade 0, n=348) [16].…”
Section: Resultsmentioning
confidence: 99%
“…The following three articles study the potential of a novel classifier HF1 based on 85 urine peptide fragments. Campbell et al [116] studied the urinary proteome of 829 individuals (622 with chronic or acute heart failure and 207 healthy controls). The study founds that the HF1 classifier allows discrimination between patients with heart fail-ure, healthy controls, and coronary heart disease (but without heart failure).…”
Section: Ce-ms Of Urine For the Determination Of Cardiovascular Diseasementioning
confidence: 99%